2005
DOI: 10.1111/j.1551-2916.2005.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium Silicate Coatings on Chemical Vapor Deposition‐SiC‐Precoated C/C–SiC: Thermodynamic Assessment and High‐Temperature Investigation

Abstract: Yttrium silicates are promising materials for improved oxidation and erosion protection for carbon fiber‐reinforced composites. A two‐layer coating system of low‐pressure plasma‐sprayed yttrium silicate on chemical vapor deposition‐SiC‐precoated C/C–SiC was tested under atmospheric re‐entry conditions simulated within a plasma wind tunnel test facility. The thermal expansion behavior of Y2SiO5 and Y2Si2O7 was investigated. The chemical compatibility with and without increasing oxygen partial pressure at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 20 publications
(42 reference statements)
0
51
0
Order By: Relevance
“…Synthesis of powders and sintering of bulk ceramics Christensen et al 39 Ogura et al 41 Parmentier et al 28 Seifert et al 40 Kumar 43 Aparicio et al 44 Sun et al Leonyuk et al 48 Zhang et al 49 Gü nther and Georg 50 Pang et al 51 Hartenbach et al , etc., via the hydrothermal method. [35][36][37][38] In this process, layered clay, saponite or smectits, is suspended in Y(NO 3 ) 3 solution, and then heated to 300uC or above in a hydrothermal tank for several days.…”
Section: Preparation Of Y-si-o Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of powders and sintering of bulk ceramics Christensen et al 39 Ogura et al 41 Parmentier et al 28 Seifert et al 40 Kumar 43 Aparicio et al 44 Sun et al Leonyuk et al 48 Zhang et al 49 Gü nther and Georg 50 Pang et al 51 Hartenbach et al , etc., via the hydrothermal method. [35][36][37][38] In this process, layered clay, saponite or smectits, is suspended in Y(NO 3 ) 3 solution, and then heated to 300uC or above in a hydrothermal tank for several days.…”
Section: Preparation Of Y-si-o Oxidesmentioning
confidence: 99%
“…Then, the coated samples were pre-oxidised in air at 1500-1600uC for 2-10 h. Finally, a layer of borosilicate glass was applied directly on their surfaces by heating at 1500uC for 2 h in Ar. Owing to the sealing effect provided by the borosilicate glass, the SiC/yttrium silicate/glass multilayer coating exhibited good oxidation protection for C/C composites in air at 1600uC for 202 h, with a weight loss of 2?87610 23 40 tested plasma-sprayed yttrium silicate coated SiC-C/C in a plasma wind tunnel at 1350uC for 23 min. The results showed that the weight change of the SiC-C/C composites with the yttrium silicate protective coating was 10% less than for the samples with only the CVD-SiC coating, and was approximately 6 times (MAN Technology) and 10 times (Astrium) lower than for the C/SiC composites from industrial suppliers.…”
Section: Slurry Dip Coatingmentioning
confidence: 99%
“…7 At present, the sol-gel process and powder-mixing route have been used for the synthesis of Y 2 SiO 5 powders. [10][11][12] In the sol-gel method, precursors of Y(NO 3 ) 3 13 It significantly lowered the sintering temperature of silicon nitride due to the presence of LiO 2 in the SiO 2 -Y 2 O 3 system, which led to formation of a low-viscosity liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…They are also ideal candidates for environmental barrier coating (EBC) and dental applications due to their excellent high temperature properties [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%